PP-028 Stability study of 1 mg/ml paediatric warfarin oral suspension in syrspend. (25th February 2017) - Guillois, G; Fetique, L; Perovic, I; Boivin, PN; Lester, MA
Abstract : Background: Warfarin (Coumadin) is the most commonly used vitamin K antagonist, a drug with a narrow therapeutic range. One suspension exists but is available for adults only and with special authorisation in some countries. The absence of a paediatric formulation means the pharmacist has to produce a magistral preparation. Purpose: The aim of this study was to determine the stability of warfarin oral suspension in Syrspend in order to establish a shelf-life for the preparation after manufacturing. Material and methods: 6 oral suspensions were prepared, using coumadine 5 mg tablets and Syrspend SF-PH4, packaged in amber vials, to protect from light, and stored at room temperature (3 batches) or at +2°C and +8°C (3 batches). Several parameters were studied on different days (0, 1, 3, 6, 10, 14, 23 and 44 (n=7)): physical stability (visual inspection, osmolality measurements) and chemical stability (pH measurement, concentrations were analysed by liquid chromatography-high resolution-UV detection (HPLC-UV) with an AT3 column, 5 µm, 4.6×150 mm). Degradation products were revealed with acid and alcalin hydrolysis (degradation over 1 hour and 16 hours). Microbiological stability was tested using colony counts on media platings. Results: After 44 days, no variation in pH or osmolality was observed. Once again, the microbiological cultures were negative. Visual inspection showed viscosity increased after 10 days. Also, concentrations were the same until 44 days and no degradation products were observed in the 6 batches. Conclusion: This study showed that 1 mg/mL warfarin oral suspension in Syrspend at room temperature, was stable for at least 44 days, so we can fix the shelf-life at 44 days. A study is in progress to determine stability at 60 days. No conflict of interest